Enhancing Creative Thinking in Vocational High School Students Through Digital History Teaching Media: The Impact of Canva Integration - Dimas Rachmat Susilo; Erlina Wiyanarti; Agus Mulyana; Wawan Darmawan (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the effectiveness of Canva-based digital teaching media in improving students' creative thinking skills in history learning at SMK Pertanian Pembangunan Lembang. The research aims to assess whether digital tools can enhance students' fluency, flexibility, originality, and elaboration in creative thinking. A Classroom Action Research (CAR) design with a mixed-method approach was implemented over three learning cycles. The study involved 64 students, divided into an experimental group (n = 32) and a control group (n = 32). Data collection instruments included the Creative Thinking Ability Test, Visual Work Assessment Rubric, and Student Response Questionnaire, validated with Cronbach’s Alpha = 0.87. Findings demonstrated a significant improvement in students’ creative thinking skills across four dimensions: fluency (M = 72.3, SD = 8.2), flexibility (M = 68.9, SD = 7.8), originality (M = 65.4, SD = 9.1), and elaboration (M = 70.2, SD = 8.5). The effect size (d = 0.82) indicated the Canva-based method’s superiority over traditional learning. Additionally, qualitative analysis showed an increase in learning motivation (85.3%) and improved quality of students’ visual works. The study provides empirical evidence that integrating digital technology in history learning enhances students’ creative thinking skills. The findings highlight the necessity of teacher professional development, adequate technological infrastructure, and contextual learning strategies for effective digital learning implementation. Canva-based digital media significantly improves creative thinking skills in vocational history education. These results suggest its potential for broader application in digital-based learning strategies within vocational education contexts.